Calculează [-3✓3-(1\3-2✓3)]×30
Răspunsuri la întrebare
Răspuns de
1
[-3✓3-(1\3-2✓3)]×30 =
= ( - 3 rad 3 -1/3 +2 rad 3) × 30 =
= ( - rad 3 -1/3 ) × 30 =
= - 30 radical 3 -10
= ( - 3 rad 3 -1/3 +2 rad 3) × 30 =
= ( - rad 3 -1/3 ) × 30 =
= - 30 radical 3 -10
parvuceanudariu:
Merci
Răspuns de
1
[-3√3-(1/3-2√3)]×30 =
= (-3√3 - 1/3 + 2√3)×30
= (-√3-1/3)×30
= -30√3 - 30/3
= -10(3√3+1)
= (-3√3 - 1/3 + 2√3)×30
= (-√3-1/3)×30
= -30√3 - 30/3
= -10(3√3+1)
Alte întrebări interesante
Engleza,
8 ani în urmă
Studii sociale,
8 ani în urmă
Chimie,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă